2017
DOI: 10.1590/0104-07072017005600015
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With the Quality of Life of Patients Undergoing Hemodialysis

Abstract: Objective: to identify factors associated with the quality of life/spirituality, religion and personal beliefs of patients with chronic kidney disease undergoing hemodialysis.Method: correlational cross-sectional study. The following instruments were applied through individual interviews: the WHOQOL-Bref, the WHOQOL-SRPB, along with a questionnaire to characterize the participants. The sample consisted of 110 participants with chronic kidney disease undergoing hemodialysis. Descriptive analysis was performed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 13 publications
1
6
0
6
Order By: Relevance
“…The comfort and well-being that faith linked to spirituality, religion and personal beliefs gives the individual a positive influence on their way of life, as well as promoting improvements in general health (28,37) . A research has indicated that patients who practice some religion have a better perception of their quality of life compared to non-practitioners, possibly associated with the support and social interaction that it provides (40) . Similar results were found in other international studies, the first one consisting of 362 patients in Iran and the second with 253 patients in Canada, in whom patients with CKD on peritoneal dialysis or hemodialysis who had some religious beliefs had a better perception of the related quality of life the health (21,27) .…”
Section: Benefits Of Spirituality And/or Religiosity In the Perceptiomentioning
confidence: 99%
See 1 more Smart Citation
“…The comfort and well-being that faith linked to spirituality, religion and personal beliefs gives the individual a positive influence on their way of life, as well as promoting improvements in general health (28,37) . A research has indicated that patients who practice some religion have a better perception of their quality of life compared to non-practitioners, possibly associated with the support and social interaction that it provides (40) . Similar results were found in other international studies, the first one consisting of 362 patients in Iran and the second with 253 patients in Canada, in whom patients with CKD on peritoneal dialysis or hemodialysis who had some religious beliefs had a better perception of the related quality of life the health (21,27) .…”
Section: Benefits Of Spirituality And/or Religiosity In the Perceptiomentioning
confidence: 99%
“…Factors associated with the quality of life of patients undergoing hemodialysis (40) . Gesualdo Religiousness, among others, had a positive influence on health-related quality of life.…”
mentioning
confidence: 99%
“…With these changes, knowledge about illness and treatment become key points for maintaining self-care, which is defined as a set of actions performed by each individual for the maintenance of health and consequent adherence to therapy. 7 In this context, functional literacy in health (FHL) arises, defined as a set of skills that involve a variety of methods, such as the ability to understand and interpret health information, written or spoken, so that they can be applied in daily life. Thus, a patient with satisfactory FHL is better able to apply prophylactic and/or therapeutic measures, compared to an individual with limited literacy level, since they have the ability to communicate and use health information that facilitates indispensable decision making regarding health issues.…”
Section: Introductionmentioning
confidence: 99%
“…5 In addition to hemodialysis treatment, a study showed that factors such as employment, marital status, gender, spirituality/religiosity, hematocrit and hemoglobin levels interfere with HRQoL. 6 Given this, it is emphasized that its evaluation is relevant because it demonstrates aspects related to the well-being of the person, satisfaction with the current state of health, directly linked to the individual perception of the effects of their disease and instituted treatments. 7 The circumstances that underlie CKD and renal replacement therapy, such as limitations that impact on biological, emotional and social aspects, can be perceived as stressful by patients.…”
Section: Introductionmentioning
confidence: 99%